Evaluation of the efficacy, safety, and side effects of secukinumab in patients with moderate-to-severe psoriasis: real-world data from a retrospective multicenter study - Ilteris Oguz Topal; Sevim Baysak; İlknur Kıvanç Altunay; Asude Kara Polat; Eylem Emel Arıkan; Ezgi Özkur; Sema Aytekin; Bilal Dogan; Tuǧba Özkök Akbulut; Filiz Topaloǧlu Demir; Ayșe Serap Karadaǧ (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background: Clinical studies have demonstrated that IL-17A inhibition with secukinumab is effective for clearing the skin of patients with psoriasis and has a favorable safety profile. Objective: The authors aim to determine whether secukinumab is effective and safe for the treatment of moderate-to-severe chronic psoriasis based on clinical experience with this drug. Method: The authors conducted a multicenter retrospective study in nine referral centers and included patients with psoriasis who had received secukinumab between March 2018 to November 2020. Data on demographic characteristics, Psoriasis Area and Severity Index (PASI) scores, and previous treatments were collected from medical records. Patients were evaluated at 12, 24, and 52 weeks with respect to response to treatment and side effects. Results: In total, 229 patients were recruited for the study. A PASI score improvement of ≥90 points over the baseline was achieved by 79%, 69.8%, and 49.3% of patients at weeks 12, 24, and 52, respectively. The most common adverse events wereCandida infections and fatigue. In total, 74 (32%) patients discontinued treatment by week 52, including due to adverse events, or secondary ineffectiveness. Study limitations: Retrospective design. Conclusions: These findings suggest that secukinumab therapy is reasonably effective in patients with moderate-to-severe psoriasis. Comorbidities and time length of the disease can affect the response to treatment. The rates of adverse events were high in this patient population.